STRATEGY OF LONG-TERM DEVELOPMENT OF RUSSIAN PENSION SYSTEM: ANALYSIS OF INTERIM RESULTS - Pavel A. Kozlov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article analyzes the level of attaining the objectives connected with improving pensioners' standard of living with simultaneous strengthening the finance stability of the pension system. The author uses methods of grouping, comparison, analysis, graphic presentation of information. He comes to the conclusion about the necessity to specify the term 'substitution index' in accordance with the accepted global norms. At the same time reaching the average level of insurance old age pensions equal to 2,5-3 living minimums runs counter to the plans to strengthen finance stability of the system. Steps connected with early retirement led to gradual increase in the number of pensioners whose pension was fixed according to general standards can affect stability of the pension system. These results could be used in the field of pension insurance.